Primary Care Providers' experiences with Pharmaceutical Care-based Medication Therapy Management Services - Heather L. Maracle; Djenane Ramalho de Oliveira; Amanda Brummel (University of Minnesota Libraries Publishing, 2012)
This study explored primary care providers' (PCPs) experiences with the practice of pharmaceutical care-based medication therapy management (MTM). Qualitative, semi-structured interviews were conducted with six PCPs who have experiences working with MTM pharmacists for at least three years. The first author conducted the interviews that were audio-taped, transcribed, and coded independently. The codes were then harmonized via discussion and consensus with the other authors. Data were analyzed for themes using the hermeneutic-phenomenological method as proposed by Max van Manen. Three men and three women were interviewed. On average, the interviewees have worked with MTM pharmacists for seven years. The six (6) themes uncovered from the interviews included: (1) "MTM is just part of our team approach to the practice of medicine": MTM as an integral part of PCPs' practices; (2) "Frankly it's education for the patient but it's also education for me": MTM services as a source of education; (3) "It's not exactly just the pharmacist that passes out the medicines at the pharmacy": The MTM practitioner is different from the dispensing pharmacist; (4) "So, less reactive, cleaning up the mess, and more proactive and catching things before they become so involved": MTM services as preventative health care efforts; (5)"I think that time is the big thing": MTM pharmacists spend more time with patients; (6) "There's an access piece, there's an availability piece, there's a finance piece": MTM services are underutilized at the clinics. In conclusion, PCPs value having MTM pharmacists as part of their team in ambulatory clinics. MTM pharmacists are considered an important source of education to patients as well as to providers as they are seen as having a unique body of knowledge äóñmedication expertise. All PCPs highly treasure the time and education provided by the MTM pharmacists, their ability to manage and adjust patients' medications, and their capability to address patients' medication experiences. MTM pharmacists are seen as being different from dispensing pharmacists, and PCPs usually highlight that difference to patients as they refer them to MTM services. Lastly, it is apparent that MTM pharmacists struggle to explain what their role is within the healthcare team and they need to find a more effective way to explain the unique value they add to the care of patients.   Type: Original Research